2011
DOI: 10.1111/j.1600-0714.2011.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem‐like cells in adenoid cystic carcinoma of salivary glands: relationship with morphogenesis of histological variants

Abstract: It is suggested that CSCs included in CD133- or CD44-positive cells play an important role in morphogenesis of salivary AdCC, especially in transition among the histological growth patterns. ECM is well known as a component of the CSC microenvironment, and ECM may regulate morphogenesis of AdCC through the stimulation of CSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
10
0
2
Order By: Relevance
“…CD133 or CD44 has been thought to represent a promising CSC marker and CD133- or CD44-positive cells play an important role in morphogenesis of salivary ACC [25,39]. In this study, we have shown that ectopic expression of c-kit in ACC-M/2 cells increases the CD133 + /CD44 + subpopulation and enhances the mammosphere forming ability, a property of the stem cells.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…CD133 or CD44 has been thought to represent a promising CSC marker and CD133- or CD44-positive cells play an important role in morphogenesis of salivary ACC [25,39]. In this study, we have shown that ectopic expression of c-kit in ACC-M/2 cells increases the CD133 + /CD44 + subpopulation and enhances the mammosphere forming ability, a property of the stem cells.…”
Section: Discussionsupporting
confidence: 52%
“…CD133 and CD44 has been regarded a cancer stem-like cell marker and CD133- or CD44-positive cells play an important role in morphogenesis of ACC[25]. To determine whether c-kit has the effect to lead to the stem cell phenotypes upon induction of EMT, we carried out Fluorescence Activating Cell Sorter (FACS) to identify CD133-positvie or CD44-positive populations.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the possible existence of CSCs has been identified in leukemia [7], breast cancer [8,9], gastric cancer [10], cervical cancer [11], and other malignancies [12,13]. The presence of CSCs in ACC is likely one of the main causes of tumor progression, metastasis, recurrence, and resistance to therapy [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Bunların yaklaşık %50'si malign özellikler gösterir. Adenoid kistik karsinom, mukoepidermoid karsinom, polimorfik düşük dereceli adenokarsinom bunlardan en sık görülenleridir 14 .…”
Section: Minör Tükürük Bezi Karsinomlarıunclassified
“…Boyun lenf nodlarına ve akciğerlere metastaz sıklıkla bildirilmiştir. Bu tümörde tedavi yaklaşımı genellikle cerrahi rezeksiyon ve postoperatif radyasyon şeklindedir 14,15 .…”
Section: Adenoid Kistik Karsinomunclassified